The Role of Brand Trust in Mediating the Influence of Social Media Marketing Features on Dugg Coffee Consumers Purchase Intention - Hasan, Fanisya Almayra Taqiyya; Aida, Nabila Mutiara; Qanita, Nazira Hayya; Kartiwa, Reka Pramesti Dwilingga; Iskandar, Berni Rahman (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
The rapid growth of social media has positioned digital platforms as essential channels for consumer engagement, particularly for small-scale businesses such as Dugg Coffee. This study investigates how four social media marketing features informativeness, interactivity, entertainment, and perceived relevance affect purchase intention, with brand trust functioning as a mediating variable. Using the Integrated Social Media Trust–Adoption Model (SMTAM), which combines elements of TAM, UTAUT, and Trust Theory, this research seeks to explain the cognitive, affective, and relational mechanisms underlying consumer behavior in digital contexts. A quantitative approach was applied through purposive sampling, collecting data from 200 respondents using an online questionnaire. The data were analyzed using PLS-SEM with SmartPLS 4 to evaluate both the measurement and structural models. The results show that informativeness, interactivity, and perceived relevance significantly influence brand trust, while entertainment does not. Furthermore, brand trust, entertainment, and perceived relevance have significant effects on purchase intention, indicating both relational and affective pathways in consumer decision-making. In contrast, informativeness and interactivity do not directly shape purchase intention, suggesting their role is primarily trust-building. IPMA findings highlight that informativeness and interactivity possess high importance yet only moderate performance, identifying them as key areas for improvement. The study contributes theoretically by reinforcing SMTAM as a comprehensive framework for understanding digital consumer behavior. Managerially, the findings emphasize the need for SMEs such as Dugg Coffee to improve content clarity, responsiveness, and relevance while delivering engaging and relatable content. Strengthening these features can enhance brand trust and ultimately increase consumer purchase intention